Good Corporate Governance Sebagai Pilar Implementasi Corporate Social Responsibility (Studi Kasus Pada PT. Akui Bird Nest Indonesia) - Ufik Novi Maslakah; Asmaul Husna; Mohamad Djasuli (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
This article aims to examine the Failure of Good Corporate Governance (GCG) Implementation in Islamic Banking in Indonesia. GCG implementation, especially in v, is very important because it can increase company profits and shareholder profits in the long term. By using normative legal methods, this article shows: First; GCG is a concept that emphasizes the importance of the right of users of financial reports to obtain accurate and timely information; and the responsibility of corporate management to provide accurate information and live up to the company's fundamental values. Second; GCG implementation failed in Indonesia. This is because there are still many Islamic banks that are hesitant to fully implement GCG. Third, Indonesia does not need more laws. What is needed is a change in the legal culture that will implement these laws and institutions as they are designed to be used and a commitment in every aspect of professional life to implement GCG.